NMR Spectroscopy–Based Metabolic Profiling of Biospecimens. (24th September 2019) - Sengupta, Arjun; Weljie, Aalim M.
Abstract: Metabolomics refers to study of metabolites in biospecimens such as blood serum, tissues, and urine. Nuclear magnetic resonance (NMR) spectroscopy and ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC‐MS/MS; mass spectrometry coupled with liquid chromatography) are most frequently employed to analyze complex biological/clinical samples. NMR is a relatively insensitive tool compared to UPLC‐MS/MS but offers straightforward quantification and identification and easy sample processing. One‐dimensional 1 H NMR spectroscopy is inherently quantitative and can be readily used for metabolite quantification without individual metabolite standards. Two‐dimensional spectroscopy is most commonly used for identification of metabolites but can also be used quantitatively. Although NMR experiments are unbiased regarding the chemical nature of the analyte, it is crucial to adhere to the proper metabolite extraction protocol for optimum results. Selection and implementation of appropriate NMR pulse programs are also important. Finally, employment of the correct metabolite quantification strategy is crucial as well. In this unit, step‐by‐step guidance for running an NMR metabolomics experiment from typical biospecimens is presented. The unit describes an optimized metabolite extraction protocol, followed by implementation of NMR experiments and quantification strategies using the so‐called "targeted profiling" technique. This approach relies on an underlying basis set of metabolite spectra acquired under similar conditions. Some strategies for statistical analysis of the data are also presented. Overall, this set of protocols should serve as a guide for anyone who wishes to enter the world of NMR‐based metabolomics analysis. © 2019 by John Wiley & Sons, Inc. Basic Protocol 1 : Metabolite extraction from different biospecimens Basic Protocol 2 : Preparation of dried upper fraction for NMR analysis Alternate Protocol : Preparation of urine samples for NMR analysis Basic Protocol 3 : NMR experiments Basic Protocol 4 : Spectral processing and quantification of metabolites Basic Protocol 5 : Statistical analysis of the data